Meningkatkan Keterampilan Sosial Siswa Melalui Penerapan Pembelajaran Kooperatif Tipe Teams Games Tournament - Fatimah, Siti; Jamal, M. Arifuddin; Suyidno, Suyidno (Universitas Lambung Mangkurat, 2013)
This research relates to the implementation of TGT in State Senior High School 12 (SMAN 12) Banjarmasin. The research objective is to describe that the Lesson Plan is well implemented, social skill, the learning result, as well as the studentsâ response through the learning process. This research is Classroom Action Research (CAR) of Hopkins model which is divided into 3 phases. To collect the data of this research is using questioners, observation, test, and documentation. The data is analyzed descriptively qualitatively and quantitatively.Â The result of the research: (1) the Lesson Plan that implemented in phase 1 is 79%, II 93%, and III 100% with very good result, (2) The studentsâ social skill enhance in every phase, (3) the result of the studentsâ learning classically enhanced, in phase I is about 56% (not passed), II 80% (not passed), and III 92% (passed). (4) the response of interest and studentâs motivation to follow cooperative learning is a good category. The conclusion is the application of cooperative learning TGT can enhance the studentsâ social skill.Â Â Â